Ethanol dry reforming over Ce-promoted NI/AI203 catalyst for H2 - Dominick, Gira (2015)
Ethanol dry reforming show a high potential to become a technology used to produce alternative fuel a transition from traditional petroleum based fuel which continue to increase in price along with its depletion. The product gas is called syngas that consists of CO and H2 gasses, whereby H2 can be used as a clean energy carrier that could help to reduce the emission of GHG. The major problem faced in this process is catalyst deactivation by coking or carbon deposition therefore a lot of effort had been done in researched of catalyst that able to prolong the reaction and also economically feasible. Recently a non noble metal Nickel (Ni) had been a great interest for catalyst for the industrial application because of its cheap in price and high C-C bond breaking activity. The results from characterization of the catalyst based on XRD analysis the calcinations and the addition of Ce promoter did not alter the composition of the catalyst hence the results show consistency with the reading from the data base. TGA analysis illustrates the addition of Ce increase the height and shifts the peaks to the left. The cracks and small catalyst size from SEM results tells that alumina has high degree of dispersion and lastly from BET study the deposition of Ce increase the diameter of catalyst however it decreases the pores surface area. Based on reaction study results by manipulating the feed partial pressure of CO2 at the highest of 50 kPa, the conversion of H2 and CO2 is at the highest up to 90 % for H2. The additions of quantity of CO2 feed ratio allow further decomposition of methane (CH4) thus increase more amount of H2 produced a consistent results with the theory. The results obtained from this research gave positive outcomes in the application of the process in industrial scale by increasing the feed ratio of CO2 to 2.5 to ethanol more H2 in being converted.